Reducing ineffective practice: Challenges in identifying low-value health care using Cochrane systematic reviews. (January 2013) - Garner, Sarah; Docherty, Mary; Somner, John; Sharma, Tarang; Choudhury, Moni; Clarke, Mike; Littlejohns, Peter
Objectives: Despite international agreement that stopping low value practices will increase efficiency, identifying them is difficult and controversial. Opponents of centralized lists of low value practices stress that the actual problem is inappropriate low value use, and better targeting and implementation of treatment thresholds is needed. Our objective was to use Cochrane Reviews to identify low value practices to support local disinvestment decisions. Methods: New or updated reviews were included if the authors concluded that the uncertain effectiveness of an intervention meant it should only be used in research, or that it was ineffective or harmful and should not be used. The reviews go through a production and quality assurance process, and are published as 'Cochrane Quality and Productivity topics' through the NHS Evidence website (http://www.library.nhs.uk/qipp/ ). Results: Over a six-month period, 65 Cochrane reviews were processed by the National Institute for Health and Clinical Excellence (NICE). Of these, 28 identified potentially low value practices in the UK context. This was primarily due to a lack of randomized evidence of effectiveness, rather than robust evidence of a lack of effectiveness, or evidence of harm. Conclusions: Identifying low-value health care practices for local disinvestment (total or partial) is both practically and politically challenging, yet it is necessary to manage health budgets. This project identified that Cochrane Reviews can potentially identify low value health care practices. However, each review has to be reinterpreted for the UK context and additional analysis has to be undertaken to facilitate local implementation. Recommendations to improve the usability of systematic reviews are made.